The GEN Z’s GREEN BEHAVIOR: HOW REAL IS IT? - Aisyah, Siti; Rizaldi, Herna; Renny Noviati Wahyuni, Eka; Belliawan Nikmah, Neta (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2025)
This study is a quantitative study consisting of 96 respondents taken from Gen Z using purposive random sampling via Microsoft Form. The study was conducted in the Pekalongan area with the aim of determining the purchasing interest in green products, namely electric motorcycles. Respondent data was tested using the Partial Least Square Structural Equation Modeling (PLS-SEM) technique with the help of the Smart PLS 4 application. The results showed that green price and green lifestyle influence green knowledge and green purchase intention. In addition, green knowledge also acts as a mediator in this relationship. REFERENSI Arif, I.H. (2024). Pengaruh Green Price terhadap minat beli tumbler starbuck dengan moderasi environmental advertising pada follower sosial media starbuck Indonesia. FEB UNM. http://repository.um.ac.id/id/eprint/354803 Baron, R. M., & Kenny, D. A. (1986). The moderator–mediator variable distinction in social psychological research: Conceptual, strategic, and statistical considerations. Journal of personality and social psychology,51(6), 1173. Chauhan, V., & Bhagat, R. (2017). Impact Analysis of Environmental Knowledge and Environmental Attitude on Purchase Intention among Young Consumers. Amity Journal of Management Research, 2(2), 59–69. Ginting, R., & Ekawati, N. (2016). Pengaruh Pengetahuan Lingkungan Terhadap Niat Membeli Produk Hijau pada Merek “Attack” dengan Kepedulian Lingkungan sebagai Variabel Mediasi. E-Jurnal Manajemen Unud, 5(4), 2223–2249. Hair, J. F., Ringle, C. M., Gudergan, S. P., Fischer, A., Nitzl, C., & Menictas, C. (2019). Partial least squares structural equation modeling-based discrete choice modeling: an illustration in modeling retailer choice. Business Research, 12(1), 115–142. https://doi.org/10.1007/s40685-018-0072-4. Pramesti, P., Cahyaningrum, Y. A. D., & Rahayu, F. (2022). Konsekuensi Dari Green Lifestyle, Product Knowledge, Dan Community. Jurnal Ekonomi Trisakti, 2(2), 555–566. Https://Doi.Org/10.25105/Jet.V2i2.14303 Putri, N., & Hayu, R. (2023). The Influence Of Environmental Knowledge, Green Product Knowledge, Green Word Of Mouth, Greenwashing, And Green Confusion As Mediator Of Green Purchase Intention. Ekombis Review: Jurnal Ilmiah Ekonomi Dan Bisnis, 12(1). Ryantari, G.A.W., & Giantari, I.G.A.K. (2020). Green Knowledge, Green Attitude, Dan Environmental Concern Berpengaruh Terhadap Niat Beli. E-Jurnal Manajemen, Vol. 9, No. 7, 2020 : 2556-2575. Saleky, S. R. J., & Souisa, W. (2019). Green Life Style Sebagai Mediator Ecoliteracy Dan Green Product Knowledge Terhadap Keputusan Pembelian Konsumen Di Kota Ambon. Specta Journal Https://Doi.Org/10.35718/Specta.V1i2.76 Of. Silvaraj, P. N. (2023). Program Studi Agribisnis Fakultas Pertanian Universitas Medan Area 2023. Simanjuntak, Y.I., Wadyatenti, M.A.D.V., & Kurniawati, L. (2025). Pengaruh Green Knowledge, Green Product, Dan Green Price Terhadap Green Purchase Intention Sepeda Motor Ramah Lingkungan. Jurnal Akuntansi, Manajemen, dan Bisnis: Parsimonia Vol 12. No. 1 Februari 2025: 7-15. Suki, N. . (2016). Green Product Purchase Intention: Impact of Green Brands, Attitude, and Knowledge. British Food Journal, 118(12), 2893–2910. https://doi.org/https://doi.org/10.1108/BFJ-06-2016-029.